2022
DOI: 10.21098/bemp.v24i4.1692
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Uncertainty and Monetary Policy Responses: Evidence From Emerging Market Economies

Abstract: This paper examines the effectiveness of monetary policy transmission in emerging economies during the COVID-19 outbreak. Using data from 14 emerging economies severely affected by the pandemic and the autoregressive distributed lag approach to cointegration, the study examines the effectiveness of monetary policy in affecting output, inflation, and credit. The study finds that: (1) In most economies, the monetary policy transmission to inflation is weakened due to the uncertainty created by the COVID-19 pande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…( Asandului et al, 2021 , Baig et al, 2021 , Behera and Rath, 2021 , Boneva et al, 2018 , Jordà et al, 2015 , Long et al, 2022 , Lovcha and Perez-Laborda, 2018 , Musunuru and Jawed, 2022 , Njindan Iyke et al, 2007 , Prabheesh et al, 2003 , Rabanal and Quint, 2013 , Salisu et al, 2021 , Sharma and Sha, 2020 , Smets, 2018 )…”
Section: Uncited Referencesmentioning
confidence: 99%
“…( Asandului et al, 2021 , Baig et al, 2021 , Behera and Rath, 2021 , Boneva et al, 2018 , Jordà et al, 2015 , Long et al, 2022 , Lovcha and Perez-Laborda, 2018 , Musunuru and Jawed, 2022 , Njindan Iyke et al, 2007 , Prabheesh et al, 2003 , Rabanal and Quint, 2013 , Salisu et al, 2021 , Sharma and Sha, 2020 , Smets, 2018 )…”
Section: Uncited Referencesmentioning
confidence: 99%
“…Conversely, Wei and Han (2021) affirmed that the emergence of this pandemic had weakened the transmission of monetary policy. Similarly, Prabheesh et al (2022) found that the monetary policy transmission during the COVID-19 crisis period is weak in emerging economies due to the “cautionary” or “wait and see” approach followed by the economic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies show the adverse effect of COVID-19 on stock market movements ([ 4 , 10 , 14 , 15 , 17 , 22 , 29 ]; and [ 24 , 25 , 27 , 28 ] [ 21 , 26 , 31 , 32 , 36 , 37 ]). However, the impact of the behaviour of foreign investors in the course of the COVID-19 pandemic on stock market movements is rare.…”
Section: Introductionmentioning
confidence: 99%